The Effect of Picture Word Card Media on Beginning Reading Ability at Grade II Students Of SDN 09 Koto Baru - Subhan, Muhammad; Saputra, Agus; Rahmatina, Rahmatina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Education The problem with learning Indonesian is students' lack of interest in reading. The use of media in learning is also inappropriate. Through this problem, the aim of this research is to overcome the low initial reading ability, so interesting and appropriate media is needed so that students can easily understand the material. The researcher will apply picture word card media. The type of research used is experiment, Pre Experimental Design. The population in this study was all class II students totaling 24 students. The development of the instrument used is a reading test in accordance with the initial reading assessment rubric. The data collection technique used was an initial test (pre-test) and a final test (post-test). The data analysis technique for this research uses the Normality Test and hypothesis testing. Based on the results of the Wilxocon test which obtained a significance of 0.000<0.05, it can be concluded that there is an influence of picture word card media on the initial reading ability of class II students at SDN 09 Koto Baru.